2015
DOI: 10.1534/g3.115.017715
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Wnt Pathway Target Genes Regulating the Division and Differentiation of Larval Seam Cells and Vulval Precursor Cells inCaenorhabditis elegans

Abstract: The evolutionarily conserved Wnt/β-catenin signaling pathway plays a fundamental role during metazoan development, regulating numerous processes including cell fate specification, cell migration, and stem cell renewal. Wnt ligand binding leads to stabilization of the transcriptional effector β-catenin and upregulation of target gene expression to mediate a cellular response. During larval development of the nematode Caenorhabditis elegans, Wnt/β-catenin pathways act in fate specification of two hypodermal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 142 publications
(154 reference statements)
0
20
0
Order By: Relevance
“…First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012). First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012). First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012).…”
mentioning
confidence: 99%
“…Previous work has identified four transcription factors regulating col gene expression. First, we showed that the L4 col genes col-38, col-49, and col-71 are regulated by the Wnt pathway transcription factor BAR-1 (beta-catenin) (Gorrepati et al, 2015;Jackson et al, 2014;Van Der Bent et al, 2015), which binds to its target genes via interaction with the TCF transcription factor POP-1 (Jackson & Eisenmann, 2012).…”
mentioning
confidence: 99%
“…Previous models consist of variations on cytoplasmic localization of the b-catenin homologs along with the APC homolog, APR-1 (Mizumoto and Sawa 2007b;Baldwin and Phillips 2014;Gorrepati et al 2015), and that it is the shuttling of these proteins, in the presence of a polarizing Wnt signal, that facilitates POP-1 (TCF) export from the nucleus in the posterior daughter cell (Sugioka et al 2011). However, a continuing question in this area remained: Is there a nuclear mechanism that sensitizes WRM-1 to export from the nucleus in the anterior daughter?…”
Section: Discussionmentioning
confidence: 99%
“…Many Wnt target genes are induced in a tissue and context-specific manner, although like other signaling cascades, Wnt signaling induces expression of negative regulators, such as SP5, Nkd1, and Axin2 (Huggins et al, 2017;Jho et al, 2002;Larraguibel et al, 2015;Yan et al, 2001). Wnt stimulation of cell lines, followed by mRNA analyses have uncovered several transcripts induced by Wnt (Gorrepati et al, 2015;Huggins et al, 2017;Jackson, Abete-Luzi, Krause, & Eisenmann, 2014;Maubant et al, 2015;Willert, Epping, Pollack, Brown, & Nusse, 2002). How these are regulated, however, remains elusive; a recent study found that only a subset of β-catenin-bound genomic loci are transcriptionally regulated by Wnt signaling, implying a further requirement for inputs to activate transcription (Nakamura, de Paiva Alves, Veenstra, & Hoppler, 2016).…”
Section: Molecular Targets Of the Wnt Signalmentioning
confidence: 99%